Diffusion of innovative soil management practices for sustainable vegetable farming - Barau, Aliyu Akilu; Haruna, Sa’adu (International Journal of Sustainable Agricultural Research, 2024)
Vegetable farmers in Sokoto state, Nigeria are disadvantaged by problem soils that are generally low in nutrient content, leading to below optimum output. As a result, this research was undertaken to disseminate innovative soil management practices through participatory on-farm trials using household waste compost, vermicompost, and biochar as treatments toward ensuring sustainable vegetable farming. The research covered a sequence of 3 main activities; including baseline survey through focus group discussion (FGD), pre and post project soil sample analyses (0-15cm and 15-30cm depths) and trials, and dissemination of findings via result demonstration, respectively. Findings from the baseline revealed that, the vegetable farmers were vulnerable and never had contact with an extension worker, living below 50/month and confronted by dwindling vegetable output due to acidity and low nutrient content of the soil. Amaranth, cabbage, lettuce, tomatoes, peppers, onions, and carrot were the mainly cultivated vegetables by the farmers. Soil management practices in the research sites were occasional application of inorganic fertilizers and traditional application of municipal waste, crop residue and refuse, which was due to inadequate knowledge on sustainable management practices of the soil. Application of organic amendments including household waste compost, vermicompost, and biochar caused tremendous variation in post-project soil properties (EC, K, Na, Ca, Mg, CEC, N, OC and P). Similarly, yield and benefit cost ratio of the trial crop (amaranth) significantly improved due to the amendments. Hence, application of organic soil amendments especially household waste and biochar would be worthwhile for sustainability of vegetable farming in Sokoto state, Nigeria.